Divide and conquer. the story of Roger Ailes [videorecording (DVD)] - Ailes, Roger (Magnolia Home Entertainment, 2019)
The filmmaker deftly fuses the personal, the political and the just plain surreal as it charts the rise and fall of Fox News Chairman, Roger Ailes. Variously called a bulldog, a kingmaker, and the Ernest Hemingway of campaign advisors, Ailes was a key media consultant to Presidents Nixon, Reagan and George H.W. Bush, powerfully shaping American political history over the last fifty years. In 2016, Ailes was forced out of Fox amid multiple allegations of sexual harassment.